A quest for genetic causes underlying signaling pathways associated with neural tube defects - Rai, Sunil; Leydier, Larissa; Sharma, Shivani; Katwala, Jigar; Sahu, Anurag (Frontiers in Pediatrics, 2023)
Neural tube defects are dreadful congenital deformities of the nervous system that occur owing to failure of normal neural tube closure. Genetic and non-genetic factors contribute to the etiology of neural tube defects in humans, indicating the role of gene-gene and gene-environment interaction in the occurrence and recurrence risk of neural tube defects. Several lines of genetic studies on humans and animals demonstrated the role of aberrant genes in the developmental risk of neural tube defects and also provide the understanding about the cellular and morphological programs that occur during the embryonic development. Other studies observed the effects of folate and supplementation of folic acid on neural tube defects. Hence, here we review what is known to date regarding altered genes associated with specific signaling pathways resulting in NTDs, as well as highlight the role of various genetic, non-genetic factors and their interaction that contribute to NTDs. Additionally, we also shine a light on the role of folate and cell adhesion molecules (CAMs) in neural tube defects.